Physiological changes and biomass partitioning as influenced by water stress in rice - KAR, IPSITA; BEHERA, BASUDEV; MISHRA, AMIT; KHANDA, CHANDRAMANI (Journal of Soil and Water Conservation, 2021)
An experiment was carried out at Central Research Farm of Orissa University of Agriculture and Technology, Bhubaneswar, Odisha during the dry seasons (January-May) of 2014 and 2015. The experiment was laid-out in a split-split plot design with two crop establishment methods, viz. dry drill direct-seeded rice (DSR) and non-puddled transplanted rice (NPTR) allocated to main-plots; three water regimes viz. no stress i.e. irrigation upto 5cm depth applied to the field as soon as the ponded water disappears, irrigation when tensiometer reads 10kPa and irrigation when tensiometer reads 40kPa allocated to sub-plots and five rice cultivars: Lalat, Sahbhagi Dhan, Arize®6129, US323 and Arize®6444 allocated to sub-sub-plots. Establishment methods had similar effect on yield, biomass partitioning and stress indices. With increase in water stress to the level of 10kPa and 40kPa, there was average yield reduction of 12% and 35%, respectively with as compared to no stress.Arize®6444 out yielded other cultivars significantly. The crop growth rate (CGR) was significantly higher under DSR till 45DAS. The average tolerance index (TOL) was lower in Sahbhagi Dhan (1.34 t ha-1) indicating it to be a stable cultivar. The mean productivity (MP), stress tolerance index (STI), geometric mean index (GMP) and harmonic mean index (HM) were higher in Arize®6444 indicating higher yield under both stress and non stress condition. Hence, it can be concluded that amongst the cultivars, Arize®6444 performs better under stress and non stress condition and there was no difference in yield due to establishment methods.